2014
DOI: 10.1124/mol.114.093666
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-Like Factor 9 Promotes Hepatic Cytochrome P450 2D6 Expression during Pregnancy in CYP2D6-Humanized Mice

Abstract: Cytochrome P450 2D6 (CYP2D6), a major drug-metabolizing enzyme, is responsible for metabolism of approximately 25% of marketed drugs. Clinical evidence indicates that metabolism of CYP2D6 substrates is increased during pregnancy, but the underlying mechanisms remain unclear. To identify transcription factors potentially responsible for CYP2D6 induction during pregnancy, a panel of genes differentially expressed in the livers of pregnant versus nonpregnant CYP2D6-humanized (tg-CYP2D6) mice was compiled via micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…CYP2D6 expression and activity also increase during pregnancy,4, 5, 6, 16 and for other CYP2D6 substrates a 2–13‐fold increase in clearance has been described 17. A previously published case series described aripiprazole plasma concentrations in three pregnancies in two women 9.…”
Section: Discussionmentioning
confidence: 97%
“…CYP2D6 expression and activity also increase during pregnancy,4, 5, 6, 16 and for other CYP2D6 substrates a 2–13‐fold increase in clearance has been described 17. A previously published case series described aripiprazole plasma concentrations in three pregnancies in two women 9.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we have shown that SHP represses and KLF9 potentiates HNF4α transactivation of CYP2D6 promoter [13, 18]. To examine whether SHP and KLF9 modulate HNF4α transactivation of Cyp2d40 promoter (similarly to CYP2D6 promoter), we performed promoter reporter assays in HEK293T cells.…”
Section: Resultsmentioning
confidence: 99%
“…HNF4α is a nuclear receptor known to play a critical role in regulating expression of liver-specific genes, including drug-metabolizing enzymes [1417]. Our studies also demonstrated that the increased HNF4α transactivation of CYP2D6 promoter is in part attributed to two transcription factors, namely small heterodimer partner (SHP, NR0B2) and Krüppel-like Factor 9 (KLF9), whose hepatic expression is differentially regulated during pregnancy [13, 18]. SHP, a member of nuclear receptor superfamily, lacks the DNA-binding domain [19] and interacts with HNF4α to function as a transcriptional repressor [20, 21].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations